Multiple Land Rights Certificate Case Settlement Review of Land Registration - Daniel Yudi Christanto; Anis Mashdurohatun (Sultan Agung Notary Law Review, 2020)
The research objective is to know and analyze completion of Multiple Land Rights Certificate in Banyumas Regency. To find out and analyze problems in resolving the case of double certified land rights in Banyumas Regency, and To find out and analyze solution against Settlement of double certified land rights cases in Banyumas Regency.This research is a qualitative research with a normative juridical approach. Based on the results of research and discussion it can be seen that "Double Land Rights Certificate Completion in Banyumas Regency”. There are two ways of resolution, namely through the mediation process at the National Land Agency (BPN) to find a solution or win-win solution, but if there is no way out through the mediation process, the settlement is carried out through the litigation process or settlement of cases in court. Constraints in resolving cases of double certified land rights in Banyumas Regency. Due to the change of the Village Head, the new Village Head who does not know that the land already has a certificate will issue a certificate sporadically based on the community's request to issue the land certificate. The problem with the National Land Agency (BPN) is that there are elements who easily issue land certificates due to various factors such as errors in issuing land certificates, both types of certificates of land ownership rights, rights to building and rights to business. Solution against settlement of double certified land rights cases by providing legal protection to the legal owner, such as case No. 26/G/2014/P.TUN.Mks and case Number 30/Pdt.G/2018/PN Pwt, namely that the Plaintiff has received protection in accordance with the applicable law, even though it has to go through a fairly long and time-consuming judicial process, because the land owner controls the land on the basis of legal and strong rights obtained in good faith, it must be protected by law.